Health Concerns of Adolescents and Adults With Spina Bifida - Starowicz, Jessica; Cassidy, Caitlin; Brunton, Laura (Frontiers in Neurology, 2021)
Due to advancements in medical care, people with spina bifida (SB) are surviving well into adulthood, resulting in a growing number of patients transitioning to an adult sector unequipped to care for people with chronic rehabilitative and medical needs. The Transitional and Lifelong Care (TLC) program is a multidisciplinary clinical service that compensates for this gap, providing comprehensive, coordinated care to adolescents, and adults with SB. As a relatively new clinical service, objective data about the patients using the service and their needs is scant. This study sought to identify the most common health concerns among TLC patients with SB at initial clinical consultation. A retrospective chart review of 94 patient charts was performed. Following data extraction, descriptive analyses were completed. The mean age of the sample was 29.04 ± 13.8 years. One hundred individual concerns and 18 concern categories were identified. On average, patients or care providers identified nine health concerns across various spheres of care, with care coordination being the most prevalent concern identified (86%). Patients also commonly had concerns regarding neurogenic bladder (70%), medications (66%), assistive devices (48%), and neurogenic bowel (42%). The numerous and wide-ranging health concerns identified support the need for individualised, coordinated care and a “medical home” for all adolescents and adults with SB during and following the transition to adult care. Health care providers caring for this population should continue to address well-documented health concerns and also consider raising discussion around topics such as sexual health, mental health, and bone health. Further research is required to understand how best to address the complex medical issues faced by adults with SB to maximise health and quality of life and improve access to healthcare.